INFLUENCE OF CUTTING DEPTH ON REGULARITIES OF PARAMETERS OF ACOUSTIC EMISSION - Філоненко, С.Ф.; Німченко, Т.В. (Proceedings of National Aviation University (archive), 2012)
We made modeling of acoustic emission by growth of cutting depth of work material that comes under plastic deformation and area of its destruction. AE impulse signals which form by the process of plastic deformation and destruction were put at the basis of a model structure. Regularities of changes of amplitude-power parameters of AE formed resulting signals were determined in the work. It is defined that by increasing of material volume, which comes under plastic deformation, and the destruction area, increasing of amplitude-power parameters of AE result signals takes place. It is shown that average amplitude level of AE result signals is increasing by linear law, and average level of energy and summary energy on the determined interval of selection is changing by non-linear laws. Increasing of energetic parameters of AE formed result signals happens faster than increasing of average level of their amplitude. It is defined that increasing of analyzed materials dispersing value happens simultaneously with increasing of amplitude-power parameters of AE result signals by increasing of volume of the material that comes under plastic deformation and the area of destruction. It is defined that in numerical ratio of dispersion increasing and standard deflection of average levels of the amplitude and AE result signals energy considerably excel increasing of its own values. Besides, increasing of dispersion and standard deviation of average levels of the amplitude and AE result signals energy have higher sensitivity to increasing of level of the examined material that comes under plastic deformation and area of destruction and can be used as informative parameters.